Identification of oxygen reduction processes at (La,Sr)MnO3 electrode/La9.5Si6O26.25 apatite electrolyte interface of solid oxide fuel cells - Cao, X.; Jiang, San Ping (Elsevier Ltd, 2013)
Oxygen reduction reaction of (La,Sr)MnO3 (LSM) cathode on La9.5Si6O26.25 apatite (LSO) electrolyte is studied over the temperature range 750–900 °C and the oxygen partial pressure range 0.01–1 atm by electrochemical impedance spectroscopy. The impedance responses show two separable arcs and are analyzed in terms of two different equivalent circuits with comparable information on the electrode processes at high and low frequencies. The electrode process associated with the high frequency arc (s1) is basically independent of oxygen partial pressure. The activation energy of s1 is 188 ± 15 kJ mol-1 for the O2 reduction reaction on the LSM electrode sintered at 1150 °C, and decreases to 120 kJ mol-1 for the O2 reduction reaction on the LSM electrode sintered at 850 °C, which is close to 80–110 kJ mol-1 observed for the same electrode process at LSM/YSZ interface. The reaction order with respect to PO2 and the activation energy of the electrode process associated with low frequency arc (s2) are generally close to that of s2 at the LSM/YSZ interface. The activation process of the cathodic polarization treatment is noticeably slower for the reaction at LSM/LSO interface as compared to that at LSM/YSZ interface. The impedance responses of O2 reduction reaction at the LSM/LSO interface are significantly higher than that at the LSM/YSZ interface due to the silicon spreading. The impedance responses decrease with the decrease of the sintering temperature of LSM electrode on LSO electrolyte. At the sintering temperature of 1000 °C, the impedance responses of O2 reduction reaction is 1.74 O cm2 at 900 °C, which is significantly smaller than that of LSM electrode sintered at 1150 °C.